Plasmogamic Paternal Contributions to Early Zygotic Development in Flowering Plants - Ohnishi, Yukinosuke; Kawashima, Tomokazu (Frontiers in Plant Science, 2020)
Flowering plant zygotes possess complete developmental potency, and the mixture of male and female genetic and cytosolic materials in the zygote is a trigger to initiate embryo development. Plasmogamy, the fusion of the gamete cytoplasms, facilitates the cellular dynamics of the zygote. In the last decade, mutant analyses, live cell imaging-based observations, and direct observations of fertilized egg cells by in vitro fusion of isolated gametes have accelerated our understanding of the post-plasmogamic events in flowering plants including cell wall formation, gamete nuclear migration and fusion, and zygotic cell elongation and asymmetric division. Especially, it has become more evident that paternal parent-of-origin effects, via sperm cytoplasm contents, not only control canonical early zygotic development, but also activate a biparental signaling pathway critical for cell fate determination after the first cell division. Here, we summarize the plasmogamic paternal contributions via the entry of sperm contents during/after fertilization in flowering plants.